Identification of The Mandeh Marine Tourism Vessel in The South Coastal District of West Sumatera Province - Afdalena Afdalena; Junaidi Junaidi; Harfiandri Damanhuri (Fakultas Perikanan dan Kelautan, Universitas Riau, 2023)
The aim of this research is to identify the Mandeh marine tourist ship in Pesisir Selatan Regency, West Sumatra Province. The method used was a survey method by taking 110 tourist respondents and 68 tourist boat business owners followed by classification and the Chi square test. The research results illustrate that tourist boats in the Mandeh marine tourism area come from 5 bases, namely Pangkalan Nagari Mandeh, Pangkalan Nagari Sungai Nyalo, Pangkalan Randang Lokan, Pangkalan TIC and Pangkalan TPI Carocok. The minimum initial investment in a tourist boat business is IDR 25,000,000 with the highest being IDR 75,000,000. The ship safety equipment owned by tourist ships is a buoy / life jacket. The numbers do not differ too much, namely from 11 to 16 per ship. 65% of ship owners promote tourist ships independently without using agent services. Furthermore, there are 16% of ship owners who use agent services to promote ships and as many as 19% of ship owners do not carry out promotions. Operational costs incurred by ship owners for 1 trip vary widely, starting from Rp. 200,000 to Rp. 450,000. Tourist boats in the Mandeh marine ecotourism area have 3 main routes with different prices. Tourists who come to visit the Mandeh marine ecotourism area come from various regions, both from West Sumatra Province and from outside West Sumatra. Most tourists from West Sumatra Province come from Padang City.